2007
DOI: 10.1086/522193
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Relations of Spiral Galaxies

Abstract: We construct a large data set of global structural parameters for 1300 field and cluster spiral galaxies and explore the joint distribution of luminosity L, optical rotation velocity V, and disk size R at I- and 2MASS K-bands. The I- and K-band velocity-luminosity (VL) relations have log-slopes of 0.29 and 0.27, respectively with sigma_ln(VL)~0.13, and show a small dependence on color and morphological type in the sense that redder, early-type disk galaxies rotate faster than bluer, later-type disk galaxies fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
394
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(447 citation statements)
references
References 87 publications
48
394
5
Order By: Relevance
“…Scatter in disc scale length comes from the empirical scatter of 0.23 dex in the luminostydisc scale length relation, determined using 144 observed galaxies (Hunter & Elmegreen 2006, Oh et al 2015, as shown in Figure 1. This is lower than the scatter of ∼0.3 dex found in Courteau et al (2007) for a larger sample of late type galaxies, but a sample which is of generally higher mass galaxies than used in this study. Fathi et al (2010) explored the relation between scale-length and stellar mass down to 10 6.6 M , and found similar scatter to Courteau et al (2007), but with lower scatter for low mass galaxies.…”
Section: Scattercontrasting
confidence: 66%
See 3 more Smart Citations
“…Scatter in disc scale length comes from the empirical scatter of 0.23 dex in the luminostydisc scale length relation, determined using 144 observed galaxies (Hunter & Elmegreen 2006, Oh et al 2015, as shown in Figure 1. This is lower than the scatter of ∼0.3 dex found in Courteau et al (2007) for a larger sample of late type galaxies, but a sample which is of generally higher mass galaxies than used in this study. Fathi et al (2010) explored the relation between scale-length and stellar mass down to 10 6.6 M , and found similar scatter to Courteau et al (2007), but with lower scatter for low mass galaxies.…”
Section: Scattercontrasting
confidence: 66%
“…This is lower than the scatter of ∼0.3 dex found in Courteau et al (2007) for a larger sample of late type galaxies, but a sample which is of generally higher mass galaxies than used in this study. Fathi et al (2010) explored the relation between scale-length and stellar mass down to 10 6.6 M , and found similar scatter to Courteau et al (2007), but with lower scatter for low mass galaxies. We tested our results using a scatter of 0.3 dex and found relatively insignificant effects that do not alter our conclusions.…”
Section: Scattercontrasting
confidence: 66%
See 2 more Smart Citations
“…The scaling law is fundamental to a better understanding of the processes of galaxy formation (e.g. Courteau et al 2007) and has been continuously used for many peculiar classes of galaxies, unlike the normal ones (e.g. Iodice et al 2003), or as a function of environment (Biviano et al 1990).…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%